The extraction of iodine-131 from the spillage using coconut shell activated carbon in nuclear medicine - Shukri, Syabil Irfan (2020)
Coconut shell is one of the agricultural by-products that have a lot of interest and uses such as it can act as biosorbents material. This study was carried out to examine the ability of adsorbents coconut shell Activated Carbon (AC) to extract the Iodine-131 from the radioactive spillage in nuclear medicine. From the literature review, the coconut shell was proven can be one of the precursors in activated carbon production. Then, the activated carbon also a common product that uses in many process applications including water purification, decolorization, deodorization, and aroma removal. Hence, coconut shell AC was also effective and efficient adsorbent for the extraction of the Iodine-131 from the radioactive spillage. The extraction of the Iodine-131 radionuclides was conducted in a batch experiment to investigate the relationship between the concentrations of the coconut shell AC and the kinetic radioactivity of iodine 131 after extraction. The concentrations of coconut shell AC that has been used were 50 mg/ml, 100 mg/ml, 150 mg/ml, 200 mg/ml, 250 mg/ml, 300 mg/ml, and 350 mg/ml. This experiment also was conducted to determine the surface morphology and element analysis of the coconut shell AC by using the FESEM and EDX. Based on the result of this experiment, there is a significant relationship between the concentrations of the coconut shell activated carbon and the kinetic radioactivity of iodine 131 after extraction. Besides, the absorption rate of the coconut shell AC also can be determined, and it stated that the absorption capabilities of coconut shell AC increase if the concentration of coconut shell AC increases. For the surface morphology, the coconut shell AC has the characteristics that each absorbent material needed, such as the highly pores and high total surface area. Lastly, for the element analysis, there was proof that the Iodine-131 has been extracted by the coconut shell AC, which is the present of the Sodium (Na) element